PEMBERDAYAAN PEREMPUAN MISKIN MELALUI KOPERASI WARGA YANG BERBASIS MASYARAKAT - Bambang Ipujono Maskun (Sosio Informa, 2003)
Poor Women Empowerment through Community Based Cooperation.This study investigated women empowerment in local community using case study method at Kelurahan Kemanggisan, Palmerah, West Jakarta. This site was choosen as the location for the studi, respresenting one of the poor enclaves in Jakarta. The purpose of this study is to know the characteristics of Kesuma Tiara as a media for empowerment process in poverty alleviation and to know how the process of empowerment performed to the members of the Kesuma Tiara Group and how the empowering processes of personal, interpersonal and political grow as the impact of the empowerment. The study has indicated that Kesuma Tiara Group has accomplished the empowerment process to its member with the outcome in the form of powerand/ or capabilities in personal, interpersonal and political, processes. Therefore, this group hassucceeded in poverty alleviation of a group of people in the grass roots level by empowering them, because women groups have the immediate and double impact on poverty in their family. This study has recommended that the activities of Kesuma Tiara Group in its effort to alleviate poverty in grassroots level group can be used as model for other cases in women empowerment to alleviate poverty.